2001
DOI: 10.1084/jem.194.8.1033
|View full text |Cite
|
Sign up to set email alerts
|

Mannose Receptor Is a Novel Ligand for L-Selectin and Mediates Lymphocyte Binding to Lymphatic Endothelium

Abstract: Continuous lymphocyte recirculation between blood and lymphoid tissues forms a basis for the function of the immune system. Lymphocyte entrance from the blood into the tissues has been thoroughly characterized, but mechanisms controlling lymphocyte exit from the lymphoid tissues via efferent lymphatics have remained virtually unknown. In this work we have identified mannose receptor (MR) on human lymphatic endothelium and demonstrate its involvement in binding of lymphocytes to lymphatic vessels. We also show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
111
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 145 publications
(114 citation statements)
references
References 37 publications
3
111
0
Order By: Relevance
“…Binding assays were performed on frozen sections of murine lymph nodes as described [30]. Briefly, frozen sections were incubated with anti-Clever-1/Stabilin-1 Ab (1.26) or negative control Ab and thereafter, lymphocytes isolated from mesenteric lymph nodes were incubated on the sections for 15 min in static conditions, followed by 5 min of rotation at 60 rpm and then again for 15 min without rotation at 71C.…”
Section: In Vitro Binding Assaysmentioning
confidence: 99%
“…Binding assays were performed on frozen sections of murine lymph nodes as described [30]. Briefly, frozen sections were incubated with anti-Clever-1/Stabilin-1 Ab (1.26) or negative control Ab and thereafter, lymphocytes isolated from mesenteric lymph nodes were incubated on the sections for 15 min in static conditions, followed by 5 min of rotation at 60 rpm and then again for 15 min without rotation at 71C.…”
Section: In Vitro Binding Assaysmentioning
confidence: 99%
“…However, the molecular mechanisms involved in lymphocyte entrance into afferent lymphatics and exit from lymph nodes via efferent lymphatics are largely unknown. Very recently we found that mannose receptor on lymphatic endothelium supports lymphocyte binding to lymphatic vessels in an L-selectin-dependent fashion [14]. The involvement of sphingosine-1-phosphate receptor in lymphocyte exit from lymph nodes has also been shown [15].…”
Section: Introductionmentioning
confidence: 99%
“…Ex vivo. In principle the adhesion assays were performed as described earlier (26). The number of lymphocytes bound to SS and LS was counted under dark-field microscopy.…”
Section: Methodsmentioning
confidence: 99%